دور الإسلام في إصلاح المسيحية: دراسة للأثر الإسلامي في الحركة البروتستانتية : (The Role of Islam in the Reform of Christianity: A Study of the Islamic Influence on the Protestant Movement) - بهاءالدين مكاوي محمد قيلي (At-Tajdid - Intellectual Refereed Journal, 2025)
The practices and corruption of the Papacy, its opposition to science, its restrictions on public freedoms, its endorsement of religious superstitions, and the sale of what became known as indulgences, led to the emergence and success of the Protestant movement and the diminishing role of the Catholic Church. A significant similarity has been observed between some of the foundations of Protestant reform and certain Islamic concepts and beliefs, raising questions about the possibility of these ideas being borrowed from Islam. Opinions on this question differ. Some thinkers believe that Protestantism is a purely Christian experience, unaffected by Islam, and that the fundamental differences between Islam and Christianity make it difficult to attribute Protestantism to any Islamic influence, suggesting that the similarities are coincidental or the result of universal human thought. Others argue that the basic ideas of Protestantism are directly borrowed from Islam. By using a range of methodologies, including historical, comparative, and analytical tracking methods, the research concluded that the significant similarity, sometimes reaching the point of exactness, combined with the strong connections between the Christian West and the Islamic world throughout history, and the proven extensive exposure of Protestants to the Quran, the Hadith, and Muslim experiences, strongly supports the hypothesis of borrowing from Islam. Keywords: Islam, Protestantism, Catholicism, papacy, indulgences.